Thermal Comfort Study Using CFD Analysis in Residential House with Mechanical Ventilation System - Usman F.; Bakar A.R.A. (Springer, 2023)
Computational fluid dynamics; Housing; Thermal comfort; Active cooling; Hybrid ventilation system; Indoor thermal comfort; Mechanical ventilation; Mechanical ventilation system; Natural ventilation; PMV, PPD; Residential house; Ventilation